Implementasi Konsep dan Pengaturan Desa Sebagai Desa Wisata Berbasis Pemberdayaan Masyarakat di Desa Rindu Hati Bengkulu Tengah - Beni Kurnia Illahi; Ardilafiza Ardilafiza; Edra Satmaidi (LPPM UNINUS, 2021)
The existence of the village is a starting point to develop and determine its position, role, and authority autonomously by developing a tourist village. Legally, Law Number 6 of 2014 concerning Villages has given positive energy to the sustainability of community welfare in the village through the development of tourist villages. The potential of tourism resources in Bengkulu is quite large, especially in Rindu Hati Village. This village has 11 types of tourism that are rarely found, including glamping, waterfalls, camping ground, tubing, rock climbing, rice fields, Putri Lake, stone boats, Supit waterfalls, the funeral of Tuanku Gagok and Raja Pembesar Alam, etc. The stages of this community service include first, identification and preliminary studies by the team, second, doing service with several techniques, which are focus group discussions, field observations, and socialization. This service resulted in Village Regulations regarding Tourism Villages and Village promotion media consisting of tourist maps and videos that would lead to village welfare.